Mental Disorders as Failures of Attention - Walter Sinnott-Armstrong; Laura K. Soter; Jesse S. Summers (Crítica)
The DSM–5 characterizes mental disorders as significant disturbances in cognition, emotion, or behavior. But what might unite the disturbances on this list? We hypothesize that mental disorders can all be meaningfully characterized as failures of attention. We understand these as failures to distribute attention in the way one has most reason to, and we include both failures of tendency and of ability. We discuss six examples of mental disorders and offer a preliminary gloss of how to recast each as centrally involving a failure of attention. We close by highlighting theoretical and practical upshots of our proposal.